Expert JavaScript - Daggett, Mark E. (Expert's voice in Web development., 2013)
Expert JavaScript is your definitive guide to understanding how and why JavaScript behaves the way it does. Master the inner workings of JavaScript by learning in detail how modern applications are made. In covering lesser-understood aspects of this powerful language and truly understanding how it works, your JavaScript code and programming skills will improve. You will learn about core fundamentals of JavaScript, including deep dives into functions, scopes, closures, and practical object-oriented code. Mark Daggett explains clearly how closures, events, and asynchronous code really operate, a.